Resolution of the Agrarian Conflict Between PT Rotorejo and Kelud Makmur Farmers on the Former Kruwuk Plantation Land - Riang Yustiva Yuniar; Mahendra Wardhana (Universitas Negeri Surabaya, 2025)
One of the plantation land conflicts that remains problematic and has yet to reach a consensus on the criminalization of agrarian conflicts is the Rotorejo Kruwuk Plantation in Gadungan Village, Gandusari District, Blitar Regency, and the Kelud Makmur Farmers Association. This study uses empirical legal research methods. The aim of the study is to identify facts related to the author's problem. The results indicate that legal resolution efforts in this agrarian conflict include mediation. Meetings held by several agencies such as the Village Head, Blitar Regency National Land Agency (BPN), the Company, the Regional Office Head, the Sub-district Head, the KPA Chair, the GTRA Team, the Gadungan Village Head, the Ministry of ATR/BPN, the Blitar City Police and the Blitar City Government in 2022 and 2023 resulted in ease in obtaining redistribution because the land status was designated as a Priority Location for Agrarian Reform. Despite the land redistribution, farmers still face obstacles in doing so, including: (1) the lack of clarity from the authorized agency regarding the legality deed; (2) the location of the proposed control does not match the PPKM's wishes; (3) the existence of land leases to other parties; (4) the existence of clashes in information and communication regarding extension of HGU; and (5) the boundary between residents' land and HGU land is not yet clear .